1972
DOI: 10.1530/jrf.0.0290215
|View full text |Cite
|
Sign up to set email alerts
|

The Concentrations of Zinc in Boar Seminal Plasma and Vesicular Secretion in Relation to Those of Nitrogenous Substances, Citrate, Galactose and Fructose

Abstract: Forty-five samples of seminal plasma obtained from eight boars and seventeen samples of vesicular secretion collected from individual boars had mean zinc contents of 22\m=.\7and 137\m=.\4 \g=m\g/ml, respectively. It was concluded that most of the zinc present in the seminal plasma of the boar is derived from the vesicular secretion.The mean concentrations of the organic constituents studied were: Seminal plasma: total nitrogen 4\m=.\42mg/ml (non-dialysable 88\m=.\7%), citrate 1 \m=.\28 mg/ml. Vesicular secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Seminal plasma and vesicular secretion samples (twenty-one and three, 458 J. C. Boursnell and E. J. Butler respectively) were collected from nine boars as described by Boursnell, Baronos, Briggs & Butler (1972). Four CGM samples were obtained as described by Boursnell et al (1970).…”
Section: Collection Of Materialsmentioning
confidence: 99%
“…Seminal plasma and vesicular secretion samples (twenty-one and three, 458 J. C. Boursnell and E. J. Butler respectively) were collected from nine boars as described by Boursnell, Baronos, Briggs & Butler (1972). Four CGM samples were obtained as described by Boursnell et al (1970).…”
Section: Collection Of Materialsmentioning
confidence: 99%
“…Gel-filtration and dialysis studies on the zinc present in boar seminal secre¬ tions (Boursnell, Briggs, Lavon & Butler, 1973) showed that, in spite of the close correlation between zinc and total nitrogen in the seminal plasma (particu¬ larly in collections from one animal) and in random vesicular secretion samples (Boursnell, Baronos, Briggs & Butler, 1972), there was no evidence of a specific association of zinc with the major protein components. The evidence that was presented suggested that other ligands, especially citrate, might be involved, offering competition for the zinc with the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The EP contains high levels of glycerylphosphorylcholine (GPC) (Dawson, Mann & White, 1957;Mann, 1959) and a considerable proportion of the nitrogenous material was soluble in ethanol (Mann, 1959). The major constituents of the VS are citrate (Humphrey & Mann, 1949), ergothioneine (Leone & Mann, 1951;Mann & Leone, 1953), inositol (Mann, 1951(Mann, , 1954 and protein (Mann, 1959;Boursnell, Baronos, Briggs & Butler, 1972). Boursnell & Coombs (1966) reported the presence of a powerful haemagglutinin in boar VS, later identified as a mixture of proteins ('protein H') of high isoelectric point by Nelson & Boursnell (1966), Boursnell & Briggs (1969) and Lavon, Briggs & Boursnell (1973).…”
Section: Introductionmentioning
confidence: 99%
“…Boursnell & Coombs (1966) reported the presence of a powerful haemagglutinin in boar VS, later identified as a mixture of proteins ('protein H') of high isoelectric point by Nelson & Boursnell (1966), Boursnell & Briggs (1969) and Lavon, Briggs & Boursnell (1973). Boursnell et al (1972) confirmed a high level ofzinc in boar VS (first observed by Bertrand & Vladesco, 1921), and also found a highly significant correlation between the zinc concen¬ tration and those of other substances characteristic of this fluid, particularly citrate and total N. The SP, a mixture of the secretions ofvarious accessory sex glands, contained large quantities of all these components.…”
Section: Introductionmentioning
confidence: 99%